Hidden Ground: Exploring an Approach to Educational Music for Strings. Issue 1 (July 2021) - Giesbrecht, Maia; Andrews, Bernard W.
This article presents the findings of a study that explored the composition of Canadian educational music. Particularly, the authors focus on the analyses of composers' scores on creating new string compositions for young musicians within the New Sounds of Learning Project. On a macro level, the composers predominantly composed multiple movements (three to four), using single section (A), binary (AB), ternary, or variation forms (A, A', A", A"', etc.), and they adopted simple meters throughout. At the micro-level, the majority of the compositions also included a technical element that was used to further skill development, that is, lack of meter to focus attention, syncopation to develop rhythmic fluency, interactive rhythms between parts to promote player coordination, modular structure to address varied skill levels, or free rhythm to promote imaginative thinking. The findings will be of interest to those members of the music profession who promote or would like to promote the dissemination of new music for strings within educational settings in Canadian music classrooms.